Elektronische Hilfsmittel: neue Möglichkeiten zur Rehabilitation Sehbehinderter - Celik, Nil; Rohrschneider, Klaus (Der Ophthalmologe, 2018)
Due to technical advances, there has been an enormous improvement of electronic vision aids in recent years. New developments are especially small portable devices which can be easily carried. The majority of electronic vision aids serve as a reading aid. Electronic magnifiers are a portable alternative to conventional screen readers. In addition, there are mobile reading devices and special computer tools. Color recognition devices and barcode scanners are helpful in everyday life. Ultrasonic orientation systems enable the recognition of obstacles also at head height. Mechanisms incorporated in shoes even comprise a navigation system. A brand new development is OrCam (OrCam Technologies Ltd., Israel), a small, inconspicuous camera system which is attached to the spectacles. It transmits vision information as a text. Smart phones and tablet personal computers have meanwhile been developed to such an extent that they replace more expensive special vision aids. Due to the immense technical progress, electronic vision aids provide visually impaired people with many elegant functions and new possibilities for ophthalmological rehabilitation. Besides the technical, mobile and financial aspects, the social acceptance of the devices, which should be as unobtrusive as possible, plays an essential role.
First Online: 10 January 2018
Gesehen am 03.04.2019